2001
DOI: 10.1177/03635465010290050601
|View full text |Cite
|
Sign up to set email alerts
|

Valgus Laxity of the Ulnar Collateral Ligament of the Elbow in Collegiate Athletes

Abstract: In this investigation, we determined the patterns of valgus laxity and acquired valgus laxity of the ulnar collateral ligament in the elbows of collegiate athletes involved in overhead and nonoverhead sports. Acquired valgus laxity of the elbow is defined as the differential amount of stress valgus opening between the dominant and nondominant elbows. Forty-eight asymptomatic male athletes involved in sports that require overhead arm movements (baseball, tennis, and swimming) and 88 asymptomatic male athletes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
26
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 16 publications
(22 reference statements)
2
26
0
Order By: Relevance
“…We did not find any significant difference in laxity between the dominant and non-dominant extremities in the goalkeepers or between the group of goalkeepers and the control group. Our results agree with findings of Singh et al 19 that no numerical value can confidently determine the pathological status of the ulnar collateral ligament of the elbow when using stress radiography.…”
Section: Discussionsupporting
confidence: 93%
“…We did not find any significant difference in laxity between the dominant and non-dominant extremities in the goalkeepers or between the group of goalkeepers and the control group. Our results agree with findings of Singh et al 19 that no numerical value can confidently determine the pathological status of the ulnar collateral ligament of the elbow when using stress radiography.…”
Section: Discussionsupporting
confidence: 93%
“…However, from the proximal attachment of the UCL on the medial epicondyle to the proximal ulna footprint, the ligament length was 24.7 mm, which was almost identical to our study and comparable with previous studies 19 . We believe that our UCL length measurements provide reasonable representations of the functional anatomic restraint of the medial elbow under valgus stress but not the actual length of the anterior band of the UCL 11 , 20 …”
Section: Discussionsupporting
confidence: 90%
“…1,15,28,39 Harada et al 18 reported that 45 of 108 young baseball players had elbow pain, and 28 players had abnormal bone fragments in the medial aspect of the elbows confirmed by ultrasonography. Meanwhile Hang et al 16 revealed that 52% of baseball pitchers had medial elbow pain, and 57% had separation of the medial epicondyle.…”
mentioning
confidence: 99%